Preconditioning of Rat Bone Marrow-Derived Mesenchymal Stromal Cells with Toll-Like Receptor Agonists - Fabiana Evaristo-Mendonça; Gabriela Sardella-Silva; Tais Hanae Kasai-Brunswick; Raquel Maria Pereira Campos; Pablo Domizi; Marcelo Felippe Santiago; Ricardo Augusto de Melo Reis; Rosalia Mendez-Otero; Victor Túlio Ribeiro-Resende; Pedro Moreno Pimentel-Coelho (Hindawi Limited, 2019)
Bone marrow-derived mesenchymal stromal cells (BM-MSCs) are dynamic cells that can sense the environment, adapting their regulatory functions to different conditions. Accordingly, the therapeutic potential of BM-MSCs can be modulated by preconditioning strategies aimed at modifying their paracrine action. Although rat BM-MSCs (rBM-MSCs) have been widely tested in preclinical research, most preconditioning studies have employed human and mouse BM-MSCs. Herein, we investigated whether rBM-MSCs modify their phenotype and paracrine functions in response to Toll-like receptor (TLR) agonists. The data showed that rBM-MSCs expressed TLR3, TLR4, and MDA5 mRNA and were able to internalize polyinosinic-polycytidylic acid (Poly(I:C)), a TLR3/MDA5 agonist. rBM-MSCs were then stimulated with Poly(I:C) or with lipopolysaccharide (LPS, a TLR4 agonist) for 1 h and were grown under normal culture conditions. LPS or Poly(I:C) stimulation did not affect the viability or the morphology of rBM-MSCs and did not modify the expression pattern of key cell surface markers. Poly(I:C) did not induce statistically significant changes in the release of several inflammatory mediators and VEGF by rBM-MSCs, although it tended to increase IL-6 and MCP-1 secretion, whereas LPS increased the release of IL-6, MCP-1, and VEGF, three factors that were constitutively secreted by unstimulated cells. The neurotrophic activity of the conditioned medium from unstimulated and LPS-preconditioned rBM-MSCs was investigated using dorsal root ganglion explants, showing that soluble factors produced by unstimulated and LPS-preconditioned rBM-MSCs can stimulate neurite outgrowth similarly, in a VEGF-dependent manner. LPS-preconditioned cells, however, were slightly more efficient in increasing the number of regrowing axons in a model of sciatic nerve transection in rats. In conclusion, LPS preconditioning boosted the production of constitutively secreted factors by rBM-MSCs, without changing their mesenchymal identity, an effect that requires further investigation in exploratory preclinical studies.